Fabrication of a photoelectrochemical aptasensor for sensitively detecting enrofloxacin antibiotic based on g-C3N4/Bi24O31Cl10 heterojunction. Issue 2 (April 2022) - Yang, Mengying; Jia, Yunfan; Chen, Yun; Yan, Pengcheng; Xu, Li; Qian, Junchao; Chen, Feng; Li, Henan
Abstract: Photoelectrochemical (PEC) aptasensor is a promising analysis platform with high selectivity and sensitivity. Exploration of photoelectric active material with excellent photoelectric conversion efficiency is the key condition to design a PEC aptasensor with excellent sensitivity. Herein, a PEC aptasensor was designed and constructed by g-C3 N4 /Bi24 O31 Cl10 heterojunction as photoelectric active material for realizing sensitive detecting enrofloxacin (ENR) antibiotic. The formation of heterojunction can facilitate separation and transfer of photogenerated carriers and reduce the recombination rate, leading to the enhancement of photocurrent response compared to that of individual semiconductor. The ENR aptamer was introduced as the specific recognition element to realize excellent selectivity of the PEC aptasensor. Because ENR-aptamer complex can block the transfer of charge, the ENR-PEC aptasensor presented the decreased photocurrent response with the increasing of ENR concentration without external voltage. The developed ENR-PEC aptasensor presented excellent sensitivity and selectivity for detecting ENR with a detection range from 0.5 to 100 fM and a low detection limit of 0.167 fM (S/N = 3). The ENR-PEC aptasensor with good reproducibility may be potential for the determination of the actual samples. Graphical Abstract: ga1 Highlights: 2D g-C3 N4 was successfully anchored on Bi24 O31 Cl10 . g-C3 N4 /Bi24 O31 Cl10 heterojunction exhibited high photoelectric performance. Aptamer as a specific recognition element improved the selectivity. The PEC aptasensor realized high sensitivity for detecting ENR.